THE EFFECT OF CARBON BLACK COMPOSITION IN STYRENE BUTADIENE RUBBER AND NATURAL RUBBER BLENDING TOWARDS ITS AGEING AND ORGANIC SOLVENT RESISTANCE PROPERTIES - Tri Susanto; Popy Marlina (Balai Riset dan Standardisasi Industri Palembang, 2019)
In terms of enhance thermal ageing resistance of natural rubber (NR) based products, it is common to blend NR with styrene butadiene rubber (SBR) to produce binary blends with higher thermal properties. However, reinforcement filler such as carbon black (CB) commonly added to improve physcomechanical properties of the blends. Thus, this present study investigated the effect of CB composition in SBR/NR binary blending towards its thermal ageing resistance and organic solvent resistance. CB was compounded 35 up to 75 phr into SBR/NR (50/50 phr), the standard procedure ASTM D-3182 was applied. The result show that hardness value increase significantly due to the higher addition CB. Conversely, the higher CB composition in SBR/NR binary blends cause quite significant the decreasing value of tensile strength and elongation at break. The effect of thermal aging properties was observed at dry air circulation at 70 oC for 48 hours. It is found that thermo-oxidative ageing cause a serious damage on the surface as well as decrease the hardness, tensile strength and elongation at break of the rubber vulcanizates. However, the effect of CB addition towards the decreasing value of those properties could not be seen clearly. In addition, toluene immersion for 24 hours cause the mass loss up to about 5% weight of the NR/SBR binary blends, whereas iso-octane and n-hexane immersion cause slight mass changes only approximately 0,1 % weight.